MODEL PEMBELAJARAN ATRAKTIF (ATTRACTIVE LEARNING) UNTUK MEMNGKATKAN MINAT BELAJAR SIS WA TAMAN KANAK-KANAK (TK) - Nelva Rolina (Jurnal Penelitian Ilmu Pendidikan, 2010)
This research has a tittle "Attractive Learning Model to Increase Learning Interest for Kindergarten Student", because of there are kindergartens which haven't attractive learning model fully. The goal of this research is increasing learning interest of kindergarten student with attractive learning model. This model is a integrated of learning, playing, and singing. So, student don't know that they are learning something. This research is a classroom action research. The subjects are students at TK Pertiwi 37 Patalan, Jetis, Bantul, DIY in group A and group B. Before do it, researcher gives trainning to 4 teachers about attractive learning model. And then, researcher does the action in 2 cyclus (every cyclus has 3 acting). The result of this research is increasing learning interest of kindergarten student. Key words: Attractive Learning Model, Learning Interest, Kindergarten Student